Pengaruh Performance Management dan Assessment Center Terhadap Kinerja Karyawan (Studi Kasus Pada PT. Bank Tabungan Negara (Persero) Kantor Cabang Malang) - Muhammad Arif Fitriawan; Achmad Sudiro (Jurnal Ilmiah Mahasiswa FEB, 2013)
This study aims to identify and analyze the effect of performance management and assessment center on the performance of employees at PT.  Bank Tabungan Negara (Persero)    Malang Branch Office, either simultaneously or partially. This research is explanatory research that explains the causal relationship between the variables through hypothesis testing. This study used a sample of 100 respondents drawn from the employees who work in PT. Bank Tabungan Negara (Persero) Malang Branch Office. Sampling was purposive sampling technique, also called judgment sampling is the selection of the type of random samples obtained by using certain considerations, generally adapted to the purpose or research problems. Test equipment used to test the research instrument beupa validity test, reliability test, and test the classical assumptions. Hypothesis testing is done using the F test and t test. Analysis using multiple linear regression analysis. From the results of research with the steps described above result that is based on the results of multiple linear regression analysis using the F test (simultaneous) it can be concluded simultaneously influencing purchasing decisions, then the results of t test analysis it can be concluded that in partial performance management and assessment center affects employee performance. Based on the results of the regression coefficient (Standardized Beta Coefficients), respectively, it can be seen variable employee performance is more influenced by variables rather than the variable assessment center performance management at PT. Savings Bank Negara (Persero) Malang Branch Office.Keywords: Performance Management, Assessment Center, Employee Performance